2005
DOI: 10.1115/1.1985431
|View full text |Cite
|
Sign up to set email alerts
|

An Optical Interferometric Band as an Indicator of Plastic Deformation Front

Abstract: The Lüders’ front and a previously discovered optical interferometric band structure were observed simultaneously in steel specimens under tensile loading. The observed Lüders’ front and optical band structure show the same propagation characteristics, confirming our previous interpretation that the optical band structure represents the plastic deformation front. Analysis shows that the stress at which the optical band structure begins to appear is approximately 10% lower than the corresponding Lüders’ front, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…Toyooka et al [14] discovered that this bright pattern actually consists of a number of concentrated parallel fringes. As reported in [15], the bright pattern is often observed near a Lüders band and propagates at the same speed. In a later stage of deformation, often this band pattern becomes stationary and the sample always fractures at that location [16].…”
Section: Experimental Observationssupporting
confidence: 56%
“…Toyooka et al [14] discovered that this bright pattern actually consists of a number of concentrated parallel fringes. As reported in [15], the bright pattern is often observed near a Lüders band and propagates at the same speed. In a later stage of deformation, often this band pattern becomes stationary and the sample always fractures at that location [16].…”
Section: Experimental Observationssupporting
confidence: 56%
“…In the transitional stage from the elastic regime to the plastic regime, optical interferometric experiments often show a band-structured, interferometric fringe pattern that can be interpreted as the onedimensional charge expressed by (42) and illustrated by Figures 9 and 10. From the similarity in various behaviors, as mentioned above, this type of one-dimensional charge can be interpreted as representing the same phenomenon as the Lüders band [Yoshida et al 2005]. Among these behaviors, the following two are interesting from the viewpoint of dynamics: (a) their drift velocity is proportional to the tensile rate and (b) the stress remains practically the same while they drift.…”
Section: Deformation As Linear Transformation Consider Inmentioning
confidence: 98%
“…The bright pattern due to the dense fringes represents the damping force proportional to ∂j x =∂x. Previous studies [17,18] have indicated that this bright pattern of dense fringes has a strong correlation with the shear band due to the Portevin-Le Chatelie effect. It is therefore considered that this pattern results from the associated …”
Section: Supporting Experimental Resultsmentioning
confidence: 93%